Anticoagulation use and clinical outcomes after catheter ablation in patients with persistent and longstanding persistent atrial fibrillation. (30th March 2018) - Liang, Jackson J.; Elafros, Melissa A.; Mullen, Michael T.; Muser, Daniele; Hayashi, Tatsuya; Enriquez, Andres; Pathak, Rajeev K.; Zado, Erica S.; Santangeli, Pasquale; Arkles, Jeffrey S.; Schaller, Robert D.; Supple, Gregory E.; et al.
Abstract: Introduction: Whether successful catheter ablation for atrial fibrillation (AF) reduces risk of cerebrovascular events (CVEs) remains controversial and whether oral anticoagulation therapy (OAT) can be safely discontinued in patients rendered free of AF recurrences remains unknown. We evaluated OAT use patterns and examined long‐term rates of CVEs (stroke/TIA) and major bleeding episodes (MBEs) in patients with nonparoxysmal AF treated with catheter ablation. Methods and results: Four hundred patients with nonparoxysmal AF (200 persistent, 200 longstanding persistent; mean age 60.3 ± 9.7 years, 82% male) undergoing first AF ablation were followed for 3.6 ± 2.4 years. OAT discontinuation during follow‐up was permitted in selected patients per physician discretion. At last follow‐up, allowing for multiple ablations, 172 (43.0%) patients were free of AF recurrence. Two hundred and seven (51.8%) discontinued OAT at some point; 174 (43.5%) were off OAT at last follow‐up. Patients without AF recurrence were more likely to remain off OAT (HR 0.23 [95% CI 0.17–0.33]). Patients with persistent (versus longstanding persistent) AF type prior to ablation (HR 0.6 [CI 0.44–0.83]) and those with CHA2 DS2 ‐VASc score <2 (HR 0.56 [0.39–0.80]) were less likely to continue OAT. Seven patients had CVEs (incidence: 0.49/100 patient years) and 14 experienced MBE during follow‐up (incidence: 0.98/100 patient years). Older age (P  =  0.001) and coronary artery disease (P  =  0.028) were associated with CVE. Conclusion: Anticoagulation discontinuation in well selected, closely monitored patients following successful ablation of nonparoxysmal AF was associated with a low rate of clinical embolic CVEs. Prospective studies are required to confirm safety of OAT discontinuation after successful AF ablation.